The Impact of Anthropocentrism on Human–Nature Relations and Its Implications for Environmental Ethics - Wahyu Dian Andriana (Journal of Language and Literature, 2025)
The escalating ecological crisis demands a fundamental shift in how humans perceive nature, including through early childhood education. This article aims to analyze the representation of anthropocentrism’s impact in Riri Cerita Anak Interaktif videos and to evaluate its implications for fostering environmental ethics in children. This study employed a descriptive-analytical approach, using flow analysis and hermeneutic techniques. Data were collected through observation and note-taking from 67 purposively selected videos on the Riri Cerita Anak Interaktif YouTube channel, based on criteria concerning the representation of anthropocentric impacts on human–nature relations and their implications for environmental ethics. The findings revealed that the videos symbolically represent the impacts of anthropocentrism through the transformation of living beings and environmental changes that emphasize ecological imbalance. The narratives embed ecocentric values such as respect for the intrinsic worth of living beings, the importance of biodiversity, limitations on exploitation, and critiques of human domination and interference with nature. Furthermore, the narratives advocate for ideological change, systemic transformation, and collective responsibility for environmental sustainability. This study concludes that Riri Cerita Anak Interaktif functions as an educational medium that conveys environmental ethics messages in an immersive manner and holds potential in shaping children's ecological awareness. The study recommends further research using audience reception approaches and extending the scope of analysis to cross-cultural children’s media to strengthen contributions to digital ecological literacy.